Clinical associations and characteristics of the polyspecific intrathecal immune response in elderly patients with non-multiple sclerosis chronic autoimmune-inflammatory neurological diseases – a retrospective cross-sectional study - Brauchle, Felix; Rapp, Daniel; Senel, Makbule; Huss, André; Dreyhaupt, Jens; Klose, Veronika; Süße, Marie; Stürner, Klarissa Hanja; Leypoldt, Frank; Tumani, Hayrettin; Lewerenz, Jan (Frontiers in Neurology, 2023)
Introduction The polyspecific intrathecal immune response (PSIIR), aka MRZ reaction (M = measles, R = rubella, Z = zoster, optionally Herpes simplex virus, HSV) is defined as intrathecal immunoglobulin synthesis (IIS) for two or more unrelated viruses. Although an established cerebrospinal fluid (CSF) biomarker for multiple sclerosis (MS), a chronic autoimmune-inflammatory neurological disease (CAIND) of the central nervous system (CNS) usually starting in young adulthood, the full spectrum of CAINDs with a positive PSIIR remains ill defined. Methods In this retrospective, cross-sectional study, patients with CSF-positive oligoclonal bands (OCB) and - to enrich for non-MS diagnoses - aged ≥50 years were enrolled. Results Of 415 with PSIIR testing results (MRZ, HSV optional), 76 were PSIIR-positive. Of these, 25 (33%) did not meet the diagnostic criteria for MS spectrum diseases (MS-S) comprising clinically or radiologically isolated syndrome (CIS/RIS) or MS. PSIIR-positive non-MS-S phenotypes were heterogenous with CNS, peripheral nerve and motor neuron involvement and often defied unequivocal diagnostic classification. A rating by neuroimmunology experts suggested non-MS CAINDs in 16/25 (64%). Long-term follow-up available in 13 always showed a chronically progressive course. Four of five responded to immunotherapy. Compared to MS-S patients, non-MS CAIND patients showed less frequent CNS regions with demyelination (25% vs. 75%) and quantitative IgG IIS (31% vs. 81%). MRZ-specific IIS did not differ between both groups, while additional HSV-specific IIS was characteristic for non-MS CAIND patients. Discussion In conclusion, PSIIR positivity occurs frequently in non-MS-S patients ≥50 years. Although sometimes apparently coincidental, the PSIIR seems to represent a suitable biomarker for previously unnoticed chronic neurologic autoimmunities, which require further characterization.